Strategi Pustakawan dalam Peningkatan Layanan Perpustakaan Berbasis Information and Communication Technology di MAN 3 Plus Keterampilan Banda Aceh - Mardhiah, Ainul; Nurmasyithah, Siti (Yayasan Putroe Ceudah Aceh, 2026)
A librarian strategy is an important step in improving library services. However, the existing library services at MAN 3 Plus Skills Banda Aceh are limited to searching for book titles. Digital services, such as e-books, are not yet available. This can be seen by the lack of technological infrastructure, including the internet's speed and stability. Therefore, it is necessary to improve more relevant digital services. The purpose of this study is to determine the librarian's strategy for improving ICT-based library services at MAN 3 Plus Skills Banda Aceh. The research method used is qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation. The subjects of this study were the library director, the librarian, and two students. The results indicate that the librarian's strategy for improving ICT-based library services at MAN 3 Plus Skills Banda Aceh involves managing the book collection through book data entry. This process involves entering book data, such as titles, author names, and publishers, into a computer system. Furthermore, the librarian uses a promotion strategy that incorporates technology, such as websites, social media, and applications, to promote ICT-based library services. This research is expected to contribute to improving ICT library services in madrasas and developing ICT-based library services.